Randomised studies of income supplementation: a lost opportunity to assess health outcomes. Issue 11 (1st November 1999) - Connor, J; Rodgers, A; Priest, P
Abstract : BACKGROUND: Despite the wealth of evidence linking low income to ill health, there is little information from randomised studies on how much and how quickly these risks can be reversed by improvements in income. OBJECTIVE: To conduct a systematic review of randomised studies of income supplementation, with particular reference to health outcomes. DESIGN: Extensive searches of electronic databases and contact with previous authors. As well as searching for trials that were specifically designed to assess the effects of increased income, studies of winners and losers of lotteries were also sought: if winning is purely chance, such studies are, in effect, randomised trials of increased income. RESULTS: Ten relevant studies were identified, all conducted in North America, mostly in the late 1960s and 1970s. Five trials were designed to assess the effects of income supplementation on workforce participation and randomised a total of 10, 000 families to 3-5 years of various combinations of minimum income guarantees and reduced tax rates. Two trials were designed to assess re-offending rates in recently released prisoners and randomised a total of 2400 people to 3-6 months of benefits. One trial was designed to assess housing allowances and randomised 3500 families to three years of income supplements. One trial assessed the health effects of 12 months of income supplementation in 54 people with severe mental illness. Finally, one study compared three groups of people who won different amounts of money in a state lottery. In all these studies the interventions resulted in increases in income of at least one fifth. However, no reliable analyses of health outcome data are available. CONCLUSIONS: Extensive opportunities to reliably assess the effects of increases in income on health outcomes have been missed. Such evidence might have increased the consideration of potential health effects during deliberations about policies that have major implications for income, such as taxation rates, benefit policies, and minimum wage levels. Randomised evidence could still be obtained with innovative new studies, such as trials of full benefit uptake or prospective studies of lottery winners in which different sized winnings are paid in monthly installments over many years.